2012
DOI: 10.1016/j.jbankfin.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The term structure of illiquidity premia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
6
48
1
Order By: Relevance
“…The rise in liquidity premia in the early 2000s -concomitant with the collapse of the Internet bubble-is also found in U.S. data by Fontaine and Garcia (2009) [72], Longstaff (2004) [102] or Feldhütter and [69]. Furthermore, Kempf, Korn and Uhrig-Homburg (2010) [95] look for liquidity factors on euro bond markets and exhibit a long-term illiquidity premium that also presents a hump in the early 2000s. The fact that the liquidity factor is particularly high during crises periods (burst of the dotcom bubble and post-Lehman periods) is consistent with the findings of Beber, Brandt and Kavajecz (2009) [16] who pinpoint that investors primarily chase liquidity during market-stress periods.…”
Section: Spainmentioning
confidence: 70%
“…The rise in liquidity premia in the early 2000s -concomitant with the collapse of the Internet bubble-is also found in U.S. data by Fontaine and Garcia (2009) [72], Longstaff (2004) [102] or Feldhütter and [69]. Furthermore, Kempf, Korn and Uhrig-Homburg (2010) [95] look for liquidity factors on euro bond markets and exhibit a long-term illiquidity premium that also presents a hump in the early 2000s. The fact that the liquidity factor is particularly high during crises periods (burst of the dotcom bubble and post-Lehman periods) is consistent with the findings of Beber, Brandt and Kavajecz (2009) [16] who pinpoint that investors primarily chase liquidity during market-stress periods.…”
Section: Spainmentioning
confidence: 70%
“…While Pan and Singleton (2008) emphasize that a signicant part of the co-movement among the term structures of sovereign CDS spreads is triggered by changes in investors appetites for credit exposure at a global level, rather than by a reassessment of the fundamental strengths of these specic sovereign economies, our results suggest that liquidity risk premium has a non-trivial role and participates directly to the variation over time of the term structure of sovereign CDS spreads. Moreover, our paper also contributes to the stream of the literature that investigates (i) the link between sovereign bond and CDS markets (Calice, Chen, and Williams 2013;among others), (ii) the interactions between credit and liquidity risks in the sovereign bond markets (Monfort and Renne 2011;Beber, Brandt, and Kavajecz 2009;Ejsing, Grothe, and Grothe 2012) and (iii) the term structure of bond market liquidity (Schuster and Uhrig-Homburg 2012;Kempf, Korn, and Uhrig-Homburg 2012;and Goyenko, Subrahmanyam, and Ukhov 2011). While most papers analyse credit and liquidity interactions, in this study we focus solely on the liquidity risk term structure for each of the sovereign CDS and bond markets.…”
Section: Introductionmentioning
confidence: 82%
“…Both eects can be interpreted in the way that an increased wariness to bear risk increases the premium of holding an illiquid bond. Kempf, Korn, and Uhrig-Homburg (2012) estimate the term structure of illiquidity premia for German Pfandbriefe. They nd a positive inuence of short-and long-term liquidation needs on the respective illiquidity premia the former proxied by asset market volatilities, the latter directly linked to a deteriorating economic outlook.…”
Section: (2008) Andmentioning
confidence: 99%
“…In this study, our primary consideration is the price term (bond spreads) of corporate bond contracts. Much literature has analyzed the influencing factors of the spreads of bonds from multiple perspectives (Gürtler & Neelmeier, 2018;Kempf, Korn, & Uhrig-Homburg, 2012). Several of the studies of firm characteristics found that large firms, more profitable firms, high disclosure quality firms, and conservative accounting firms issued lower spreads on bonds (Ahmed, Billings, Morton, & Stanford Harris, 2002;Samet & Obay, 2014;Sengupta, 1998).…”
Section: Institutional Backgrounds Of Corporate Debt In Chinamentioning
confidence: 99%